Malti-Douglas, Fedwa. Medicines of the soul. Female Bodies and Sacred Geographies in a Transnational Islam. Berkeley, Los Angeles, Londres, University of California Press, 2001, p. 223 - Western, Wilda Celia (Estudios de Asia y África, 2002)
-